Processed Food and Atopic Dermatitis: A Pooled Analysis of Three Cross-Sectional Studies in Chinese Adults - Li, Yajia; Su, Juan; Luo, Dan; Duan, Yanying; Huang, Zhijun; He, Meian; Tao, Juan; Xiao, Shuiyuan; Xiao, Yi; Chen, Xiang; Shen, Minxue (Frontiers in Nutrition, 2021)
Objective: The effect of processed foods on atopic dermatitis (AD) in adults is unclear. This study was to evaluate the association between processed foods and AD in the Chinese adult population. Design: This study included three population-based cross-sectional studies using cluster sampling by villages, institutions, or factories. Participants underwent dermatological examinations by certiﬁcated dermatologists and a food frequency questionnaire survey. A spot urine sample was collected to estimate the daily sodium intake. Odds ratios (aORs) and 95% confidence intervals (CIs) were presented as the effect size. Setting: Shiyan city of Hubei province, and Huayuan, Shimen, Hengyang, Zhuzhou, and Changsha of Hunan province. Participants: Automobile manufacture workers from Shiyan of Hubei province, and rural residents and civil servants from Hunan. Results: A total of 15062 participants, including 3781 rural residents, 5111 civil servants, and 6170 workers, completed all evaluations. Compared to those hardly consumed pickles, consumption of pickles 1–3 times per week was significantly associated with AD (aOR: 1.35; 95% CI: 1.06–1.70). The intake of processed meats 1–3 times per month (aOR: 1.29; 95% CI: 1.05–1.58) and 1–3 times per week (aOR: 1.44; 95% CI: 1.11–1.87) were associated with AD dose-dependently when compared with those who rarely ate processed meats. Compared with non-consumers, the consumption of any processed foods 1–3 times per week (aOR: 1.39; 95% CI: 1.08–1.80) and ≥4 times per week (aOR: 1.41; 95% CI: 1.05–1.89) showed increased risks of AD. A positive association of estimated sodium intake with AD was also observed. Conclusions: Intake of processed foods is associated with AD in Chinese adults.